POLA PERSEBARAN NITRAT DAN PHOSPHAT DENGAN MODEL AQUATOX2.2 SERTA HUBUNGAN TERHADAP TANAMAN ENCENG GONDOK PADA PERMUKAAN DANAU (STUDI KASUS DANAU RAWA PENING KABUPATEN SEMARANG) - Budihardjo, Mochamad Arief; Huboyo, Haryono Setiyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Rawa Pening meets with environment degradation like other lakes in Indonesia which is caused by pollutant from the outside especially nitrate and phosphate. Degradation that is happened in this  time is  water  hyacinth  blooms  (enceng  gondok)  on  the  surface  of  the  lake.  This  makes Rawa Pening’s function become annoyed such as  PLTA, tourism, fishery, and irrigation. This degradation keeps  going  and  tends  to  increase  so  that  it  is  necessary  to  do  nitrate  and phosphate monitoring for next time. The taking of sample has done at three points: upstream (S1),  middle (S2), and  downstream  (S3)  which  are  used  as  an  observed  data.  Method  used  research is predicting nitrate and phosphate concentration for ten years later by Aquatox 2.2. Model  validation  done  with compare  observed  result  and  model  result.  Mean  error  from  this validation  less  than  5%  so that  the  model  supposed  describe  the  field  conditions.  Simulation model  result  that  obtained for  ten  years  later  are  nitrate  0,037  mg/L  (S1);  0,035  mg/L  (S2); 0,032 mg/L (S3) and phosphate 0,296 mg/L (S1); 0,274 mg/L (S2); 0,262 mg/L (S3). Dispersion pattern of simulation model result made by dividing lake into three segment, then search current velocity  to  get  dispersion distance.  This  pattern  showed  that  nitrate  and  phosphate concentration progressively decline from S1 to S3. Based on this pattern is knowable enceng gondok  amount  estimation  also  progressively decline  from  S1  to  S3.  The  calculation  sum  of enceng gondok estimation in upstream is about 66 plants and in downstream is about 43 plants. The width of enceng gondok progressively decline according to the amount of enceng gondok in every contour. But the density of enceng gondok not decline because the differences of every contour  area.  Support  energy  of  Rawa  Pening  surface area  to  enceng  gondok  is  about 180.594,59 m² and support energy of the  enceng gondok’s total is about 14.054 plants. Wet longitudinal section daily loads of Rawa Pening is about 6.319.405,41 m².